2019
DOI: 10.1186/s13046-019-1189-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term fasting on cancer treatment

Abstract: Growing preclinical evidence shows that short-term fasting (STF) protects from toxicity while enhancing the efficacy of a variety of chemotherapeutic agents in the treatment of various tumour types. STF reinforces stress resistance of healthy cells, while tumor cells become even more sensitive to toxins, perhaps through shortage of nutrients to satisfy their needs in the context of high proliferation rates and/or loss of flexibility to respond to extreme circumstances. In humans, STF may be a feasible approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 141 publications
3
96
0
5
Order By: Relevance
“…Similarly to de Groot et al 9, we found a significant reduction of IGF-1 during mSTF. This reduction of IGF-1 seems to be one of the key mediators of differential stress resistance in response to nutrient restriction (36) healthy adults (38). While de Groot et al (9) revealed no change of fT3, we found a significant reduction of fT3 during KD in our previous trial in healthy subjects (38).…”
Section: Discussionsupporting
confidence: 42%
“…Similarly to de Groot et al 9, we found a significant reduction of IGF-1 during mSTF. This reduction of IGF-1 seems to be one of the key mediators of differential stress resistance in response to nutrient restriction (36) healthy adults (38). While de Groot et al (9) revealed no change of fT3, we found a significant reduction of fT3 during KD in our previous trial in healthy subjects (38).…”
Section: Discussionsupporting
confidence: 42%
“…There is growing evidence that short-term fasting can improve patient response to cancer chemotherapy, whilst providing protection from toxicity [28].…”
Section: Metabolic Effects Of Controlled and Ramadan Fastingmentioning
confidence: 99%
“…La evidencia muestra que el ayuno protege de la toxicidad al tiempo que mejora la eficacia de una variedad de quimioterapéuticos en el tratamiento de varios tipos de tumores (23) .…”
Section: Cáncerunclassified